Factors related to accident, illness and stress of secondary school teachers in the Klang Valley, Malaysia - Tai, Kwee Ling (2019)
Similar to other occupations, teachers are exposed to various safety and health hazards in school during the long working hours they spend in their workplace. Interestingly, the general public may not have realized this fact or even if being aware, may not have thought that their safety, health, and welfare bear collective significance towards the future of the country. There has been a lack of focus on occupational safety and health (OSH) issues among teachers in Malaysia. This study aimed to determine the prevalence and predictors associated with the illness among secondary schools’ teachers in a different location of school in Malaysia. This cross-sectional study was carried out among secondary schools’ teachers in Klang Valley. Two hundred and twelve respondents who fulfilled the study criteria volunteered to participate in the study using stratified sampling methods. A self-administered questionnaire was used, which consist of six main sections: socio-demographic characteristics, teaching background, knowledge and experience in OSH issues, workplace accident, illness, and psychological factors. The types of the accident in the questionnaire were adapted based on the Social Security Organisation (SOCSO)’s Annual Report whereas illness adapted from Subjective Health Complaints Inventory (SHC) while Depression Anxiety Stress Scales 21 items (DASS 21) was used to determine psychological status among respondent. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The prevalence of illness was 81.9%. School location (p = 0.004), having other professional roles in school besides teaching (p = 0.010), total amount of other professional roles (p = 0.046), number of subject teaching (p = 0.040), and anxiety (p = 0.002) were significantly associated with the prevalence of illness. Rural school teachers (OR = 0.310, p = 0.017) have lower odds to have an illness whereas teachers with two or more subjects teaching (OR = 3.001, p = 0.026), participated in safety-related training activities (OR = 3.924, p = 0.022), with anxiety symptom (OR = 7.033, p = 0.005), and being involved in school accident in the past year (OR = 4.414, p = 0.015) have higher odds of having an illness. It appeared that there are causes to be concerned based on the findings in this study. The prevalence of illness although self-reported should not be taken lightly as the symptoms regardless of being psychosomatic or psychophysiology can potentially affect the performance and teachers. In the spirit of the Occupational Safety and Health Act (1994), it is the responsibility of the Ministry of Education to ensure the safe and healthy workplace environment of the teachers in the school. Working together with other stakeholders, further investigation nationwide should be carried out to determine and develop a policy to mitigate the Occupational Safety and Health issues among the teachers.